Deus ex Machina : da fundamentação à desfundamentação do transconstitucionalismo - Arruda, Octaviano Padovese de (2011)
This paper assumes that the conflict between positive law and natural law and all the historical construction that both rationalities have is not enough to describe the advent of phenomenon of transconstitutionalism. Several other legal constructions such as Critical Legal Studies, Law and Economics and the emphasis on a theory of language also have their own limits, within the theory itself prevents them to describe satisfactory the emergence of tranconstitutionals problems. The paper presents three different theories in order to provide a support for a construction of general theory of transconstitutionalism or at least being a guide for legal practices, for constitutionalist, for international lawyers and political scientists to reshaping the conflicts between different legal systems or rationalities justifies the reference in a legal decision of a particular system does not the other. The three models will be explored as follows: the theory of communicative action of Jürgen Habermas; Jacques Derrida s descontruction; and Niklas Luhmann s self reference system. As for Habermas, assuming there is the possibility of rationality support the right of where transconstitutional Habermas indicates how the rights to Medium to reduce the tension between factcity and validity. Jacques Derrida's theory of the concept of Gewalt transported to the transconstitucionalismo transconstitucionalismo and would be capable of achieving justice. As for Niklas Luhmann, face problems of various levels of the Constitution that emerge in society and how the world can transconstitucionalismo autofundamentar constitutionally from the multiplicity of levels inviolable. Finally, coming out of the structural transconstitucionalismo, we will consider a possible way of learning and adaptation between the courts transconstitucionais